Austenitic stainless steel material, its manufacturing method, and corrosion-resistant member
By irradiating laser light to remove oxide scales and controlling inclusion density in austenitic stainless steel materials, the process achieves a smooth, glossy surface with improved corrosion and fatigue properties, addressing the limitations of conventional descale methods.
Patent Information
- Application Number
- JP2021058778
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Conventional descale processes for austenitic stainless steel materials using pickling result in uneven surfaces, loss of gloss, and exposure of inclusions, which reduce corrosion resistance and fatigue properties.
The development of an austenitic stainless steel material with a specific composition and a manufacturing method that involves irradiating laser light to remove the oxide scale, controlling the number density of inclusions, and forming a melt solidification layer to improve surface smoothness and corrosion resistance.
The approach results in a smooth, glossy surface with enhanced corrosion resistance and fatigue properties, improving the designability and performance of austenitic stainless steel materials.
Smart Images

Figure 0007666967000003 
Figure 0007666967000004 
Figure 0007666967000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel material, a manufacturing method thereof, and a corrosion-resistant member. [Background technology]
[0002] Stainless steel materials have various excellent properties such as corrosion resistance, and are therefore used in a wide range of applications, such as automobile parts, building parts, and kitchen utensils. Stainless steel materials are classified into steel plates, steel bars, steel strips, steel bars, steel pipes, etc., depending on the shape. Stainless steel plates, which are common stainless steel materials, are manufactured by the following process. For example, hot-rolled steel plates (thick plates) are manufactured by continuously casting molten iron, which is made by dissolving stainless steel raw materials, into slabs, hot rolling the slabs, and then annealing and pickling. Cold-rolled steel plates (thin plates) are manufactured by cold-rolling the hot-rolled steel plates, followed by annealing and pickling. In such a manufacturing process for stainless steel materials, pickling is performed to remove oxide scale formed on the surface of the stainless steel material. Hereinafter, removing oxide scale formed on the surface of the stainless steel material will be referred to as "descaling".
[0003] However, there are cases where oxide scale cannot be sufficiently removed by pickling alone. In particular, among stainless steel materials, austenitic stainless steel materials have excellent acid resistance due to their high Ni content. Therefore, it is more difficult to remove oxide scale formed on the surface of austenitic stainless steel materials by pickling compared to other stainless steel materials. Therefore, in a typical descaling process, a mechanical pretreatment such as a scale breaker or shot blasting is performed to crack the oxide scale, and then the oxide scale is pickled to make it easier to remove (for example, Patent Documents 1 and 2). In addition, a method of immersing the stainless steel material in a salt bath as a chemical pretreatment is also known. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-172077 A [Patent Document 2] Japanese Patent Application Publication No. 2-145785 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the conventional descaling process using pickling, the surface unevenness formed by the pretreatment and the surface roughness caused by the pickling cause the surface of the stainless steel material to turn white and lose its luster, resulting in a decrease in design. In particular, since a higher level of design (smoothness and gloss) is required for cold-rolled steel material compared to hot-rolled steel material, it is difficult to obtain the desired design with the conventional descaling process using pickling. In addition, when the oxide scale is removed, inclusions are exposed on the surface of the stainless steel material, and these inclusions are a factor in decreasing the corrosion resistance and fatigue properties of the stainless steel material. In order to solve these problems, it is conceivable to polish the surface after the descaling process, but polishing the surface until it is smooth increases the amount of grinding, reducing the yield, and also reduces corrosion resistance and design properties due to polishing burns and entrapment of polishing debris. Furthermore, since inclusions are also present inside the stainless steel material, new inclusions will be exposed on the surface of the stainless steel material even if the surface is polished after the descaling process. Therefore, this method cannot be said to be effective.
[0006] The present invention has been made to solve the above-mentioned problems, and has an object to provide an austenitic stainless steel material having a smooth and glossy surface and excellent corrosion resistance and fatigue characteristics, a method for producing the same, and a corrosion-resistant component using the same. [Means for solving the problem]
[0007] As a result of intensive research to solve the above problems, the inventors have found that by controlling the composition of an austenitic stainless steel material and irradiating it with a laser beam under specific conditions, it is possible to descale the material while maintaining the smoothness and gloss of the surface, and to dissolve the inclusions on the surface, thereby improving the corrosion resistance and fatigue properties. Based on this finding, the inventors have produced and examined various austenitic stainless steel materials, and found that an austenitic stainless steel material having a specific composition and a ratio D2 / D1 of the number density D2 of inclusions on the surface to the number density D1 of a specific inclusion in the parent phase at a depth of 1 / 4 of the thickness from the surface can solve the above problems, thereby completing the present invention.
[0008] That is, the present invention provides a composition comprising, on a mass basis, C: 0.001 to 0.150%, Si: 1.00% or less, Mn: 2.50% or less, P: 0.050% or less, S: 0.0300% or less, Ni: 6.00 to 26.00%, Cr: 15.00 to 26.00%, Mo: 8.00% or less, Cu: 4.00% or less, N: 0.400% or less, Al: 0.400% or less, Si+2Al is less than 1.20%, and the balance is Fe and impurities; The ratio D2 / D1 of the number density D2 of the inclusions on the surface to the number density D1 of the inclusions having a circle equivalent diameter of 0.5 to 10 μm in the parent phase at a position where the depth from the surface is 1 / 4 of the thickness is 0.50 or less. and the number density D2 of the inclusions on the surface is 75 pieces / mm 2 is less than or equal to It is an austenitic stainless steel material.
[0009] The present invention also provides a method for producing a semiconductor device comprising the steps of: A method for producing the austenitic stainless steel material, comprising the steps of:The method includes a descaling step of irradiating a cold-rolled steel material having a composition, on a mass basis, of C: 0.001 to 0.150%, Si: 1.00% or less, Mn: 2.50% or less, P: 0.050% or less, S: 0.0300% or less, Ni: 6.00 to 26.00%, Cr: 15.00 to 26.00%, Mo: 8.00% or less, Cu: 4.00% or less, N: 0.400% or less, Al: 0.400% or less, Si+2Al being less than 1.20%, and the balance being Fe and impurities, with a laser beam to remove oxide scale formed on a surface of the cold-rolled steel material. fruit , The laser light irradiation is performed under conditions capable of melting a region of the cold-rolled steel material from the interface between the parent phase and the oxide scale to a depth of 0.50 to 10.00 μm. How to It is law.
[0010] Furthermore, the present invention is a corrosion-resistant member comprising the austenitic stainless steel material. Effect of the Invention
[0011] According to the present invention, it is possible to provide an austenitic stainless steel material having a smooth and glossy surface and excellent corrosion resistance and fatigue properties, a method for producing the same, and a corrosion-resistant member using the same. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view of an austenitic stainless steel material according to an embodiment of the present invention. [Diagram 2] 1A and 1B are schematic cross-sectional views for explaining the difference between descaling by irradiation of laser light and descaling by a conventional method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0014] The austenitic stainless steel material according to an embodiment of the present invention has a composition containing C: 0.001 to 0.150%, Si: 1.00% or less, Mn: 2.50% or less, P: 0.050% or less, S: 0.0300% or less, Ni: 6.00 to 26.00%, Cr: 15.00 to 26.00%, Mo: 8.00% or less, Cu: 4.00% or less, N: 0.400% or less, Al: 0.400% or less, with Si+2Al being less than 1.20%, and the balance being Fe and impurities. Here, in this specification, "stainless steel material" means a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate (including a strip), a bar, and a tube. In addition, the cross-sectional shape may be various shaped steel such as a T-shape and an I-shape. In addition, "impurities" refer to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes when industrially manufacturing stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, stainless steel materials may contain 0.02% or less of O as an impurity.
[0015] In addition, the austenitic stainless steel material according to the embodiment of the present invention may further contain one or more selected from Ti: 0.001 to 0.500%, Nb: 0.001 to 1.000%, V: 0.001 to 1.000%, W: 0.001 to 1.000%, Zr: 0.001 to 1.000%, and Co: 0.001 to 1.200%. Furthermore, the austenitic stainless steel material according to the embodiment of the present invention may further contain one or more selected from Ca: 0.0001 to 0.0100%, B: 0.0001 to 0.0080%, Sn: 0.001 to 0.500%, and REM: 0.200% or less. Hereinafter, each component will be described in detail.
[0016] <C: 0.001 to 0.150%> If the C content is too high, in addition to becoming hard and reducing workability, sensitization occurs when subjected to thermal effects such as welding, and the corrosion resistance of the austenitic stainless steel material decreases. Therefore, the upper limit value of the C content is controlled to 0.150%, preferably 0.100%, more preferably 0.060%, and still more preferably 0.040%. On the other hand, if the C content is too low, it leads to deterioration of workability due to a decrease in the stability of the austenite phase and an increase in refining costs. Therefore, the lower limit value of the C content is controlled to 0.001%, preferably 0.002%, more preferably 0.005%, and still more preferably 0.010%.
[0017] <Si: 1.00% or less> If the Si content is too high, it hardens and the workability of the austenitic stainless steel material decreases. Therefore, the upper limit value of the Si content is controlled to 1.00%, preferably 0.80%, more preferably 0.70%, and still more preferably 0.60%. On the other hand, the lower limit value of the Si content is not particularly limited, but is preferably 0.01%, more preferably 0.05%, and still more preferably 0.10%.
[0018] <Mn: 2.50% or less> Mn is an austenite phase (γ-phase) forming element. If the Mn content is too high, the corrosion resistance of the austenitic stainless steel material decreases. Therefore, the upper limit value of the Mn content is controlled to 2.50%, preferably 2.00%, more preferably 1.50%, and still more preferably 1.00%. On the other hand, the lower limit value of the Mn content is not particularly limited, but is preferably 0.01%, more preferably 0.05%, and still more preferably 0.10%.
[0019] <P: Below 0.050%> If the content of P is too high, the corrosion resistance and workability of the austenitic stainless steel material will deteriorate. Therefore, the upper limit value of the content of P is controlled to 0.050%, preferably 0.035%, more preferably 0.030%, and still more preferably 0.020%. On the other hand, the lower limit value of the content of P is not particularly limited, but is preferably 0.001%, more preferably 0.005%, and still more preferably 0.010%.
[0020] <S: Below 0.0300%> If the content of S is too high, the hot workability will decrease, the manufacturability of the austenitic stainless steel material will deteriorate, and it will also have an adverse effect on the corrosion resistance. Therefore, the upper limit value of the content of S is controlled to 0.0300%, preferably 0.0100%, more preferably 0.0050%, and still more preferably 0.0010%. On the other hand, the lower limit value of the content of S is not particularly limited, but is preferably 0.0001%, more preferably 0.0002%, and still more preferably 0.0003%.
[0021] <Ni: 6.00 - 26.00%> Ni is an austenite phase (γ-phase) forming element like Mn. Since Ni is expensive, if the content is too high, it will lead to an increase in the manufacturing cost. Therefore, the upper limit value of the content of Ni is controlled to 26.00%, preferably 25.50%. On the other hand, if the content of Ni is too low, the corrosion resistance of the austenitic stainless steel material will deteriorate. Therefore, the lower limit value of the content of Ni is controlled to 6.00%, preferably 10.00%, more preferably 12.00%, and still more preferably 18.00%.
[0022] <Cr: 15.00 - 26.00%> If the Cr content is too high, it will not only lead to an increase in refining costs, but also harden due to solid solution strengthening, resulting in a decrease in the workability of austenitic stainless steel. Therefore, the upper limit of the Cr content is controlled to 26.00%, preferably 24.00%, more preferably 22.00%, and even more preferably 20.50%. On the other hand, if the Cr content is too low, sufficient corrosion resistance cannot be obtained. Therefore, the lower limit of the Cr content is controlled to 15.00%, preferably 16.00%, more preferably 17.00%, and even more preferably 18.00%.
[0023] <Mo: 8.00% or less> Mo is an element that improves the corrosion resistance of austenitic stainless steel. Since Mo is expensive, if the Mo content is too high, it will lead to an increase in manufacturing costs. Therefore, the upper limit of the Mo content is controlled to 8.00%, preferably 7.50%, more preferably 7.00%, and even more preferably 6.50%. On the other hand, the lower limit of the Mo content is not particularly limited, but is preferably 0.20%, more preferably 2.00%, even more preferably 5.50%, and particularly preferably 6.00%.
[0024] <Cu: 4.00% or less> Cu is an element that improves the workability of austenitic stainless steel. If the Cu content is too high, the corrosion resistance of austenitic stainless steel will decrease, and a low melting point phase will be formed during casting, leading to a decrease in hot workability. Therefore, the upper limit of the Cu content is controlled to 4.00%, preferably 3.50%, more preferably 2.00%, and even more preferably 1.00%. On the other hand, the lower limit of the Cu content is not particularly limited, but is preferably 0.20%, more preferably 0.40%.
[0025] <N: 0.400% or less> N is an element that improves corrosion resistance. If the content of N is too high, it will harden and reduce the workability of austenitic stainless steel materials. Therefore, the upper limit value of the content of N is controlled to be 0.400%, preferably 0.300%, more preferably 0.250%, and still more preferably 0.230%. On the other hand, the lower limit value of the content of N is not particularly limited, but is preferably 0.010% and preferably 0.020%.
[0026] <Al: 0.400% or less> Al is an element that is added as necessary for deoxidation in the refining process and improves corrosion resistance and heat resistance. If the content of Al is too high, the amount of inclusions generated will increase and the quality will deteriorate. Therefore, the upper limit value of the content of Al is controlled to be 0.400%, preferably 0.100%, and more preferably 0.050%. On the other hand, the lower limit value of the content of Al is not particularly limited, but is preferably 0.001% and more preferably 0.005%.
[0027] <Si + 2Al: less than 1.20%> The austenitic stainless steel material according to the embodiment of the present invention targets those with low contents of Si and Al. Specifically, Si + 2Al (each element symbol represents the content of each element) is less than 1.20%, preferably 1.10% or less, more preferably 1.00% or less, and still more preferably 0.90% or less. The lower limit value of Si + 2Al is not particularly limited, but is preferably 0.01%, more preferably 0.05%, and still more preferably 0.10%.
[0028] <Ti: 0.001 - 0.500%> Ti is an element that improves corrosion resistance and intergranular corrosion resistance by combining with C and N, and is added as necessary. From the viewpoint of obtaining the effect of Ti, the lower limit of the Ti content is controlled to 0.001%, preferably 0.005%. On the other hand, if the Ti content is too high, it causes surface defects, leading to a decrease in quality and a decrease in workability of the austenitic stainless steel material. Therefore, the upper limit of the Ti content is controlled to 0.500%, preferably 0.300%, more preferably 0.100%.
[0029] <Nb:0.001~1.000%> Nb, like Ti, is an element that combines with C and N to improve corrosion resistance and intergranular corrosion resistance, and is added as necessary. From the viewpoint of obtaining the effect of Nb, the lower limit of the Nb content is controlled to 0.001%, preferably 0.004%, and more preferably 0.010%. On the other hand, if the Nb content is too high, the workability of the austenitic stainless steel material decreases. Therefore, the upper limit of the Nb content is controlled to 1.000%, preferably 0.600%, and more preferably 0.060%.
[0030] <V:0.001~1.000%> V is an element that improves corrosion resistance and is added as necessary. From the viewpoint of obtaining the effect of V, the lower limit of the V content is controlled to 0.001%, preferably 0.010%. On the other hand, if the V content is too high, the workability of the austenitic stainless steel material decreases. Therefore, the upper limit of the V content is controlled to 1.000%, preferably 0.200%.
[0031] <W:0.001~1.000%> W is an element that improves high-temperature strength and corrosion resistance, and is added as necessary. From the viewpoint of obtaining the effects of W, the lower limit of the W content is controlled to 0.001%, preferably 0.010%. On the other hand, if the W content is too high, the material becomes hard and the workability decreases, and the surface defects increase, degrading the surface quality of the austenitic stainless steel material. Therefore, the upper limit of the W content is controlled to 1.000%, preferably 0.300%.
[0032] <Zr:0.001~1.000%> Zr is an element that improves oxidation resistance and intergranular corrosion resistance by combining with C and N, and is added as necessary. From the viewpoint of obtaining the effect of Zr, the lower limit of the Zr content is controlled to 0.001%, preferably 0.010%. On the other hand, if the Zr content is too high, the workability of the austenitic stainless steel material is reduced. Therefore, the upper limit of the Zr content is controlled to 1.000%, preferably 0.200%, more preferably 0.050%.
[0033] <Co:0.001~1.200%> Co is an element that improves heat resistance and is added as necessary. From the viewpoint of obtaining the effect of Co, the lower limit of the Co content is controlled to 0.001%, preferably 0.010%. On the other hand, since Co is expensive, if the Co content is too high, the manufacturing cost increases. Therefore, the upper limit of the Co content is controlled to 1.200%, preferably 0.400%.
[0034] <Ca:0.0001~0.0100%> Ca is an element that improves the hot workability of austenitic stainless steel materials and is added as necessary. Ca is also an element that improves intergranular oxidation resistance by forming sulfides and suppressing grain boundary segregation of S. From the viewpoint of obtaining the effect of Ca, the lower limit of the Ca content is controlled to 0.0001%, preferably 0.0003%. On the other hand, if the Ca content is too high, the number of inclusions increases, leading to a decrease in workability. Therefore, the upper limit of the Ca content is controlled to 0.0100%, preferably 0.0050%.
[0035] <B: 0.0001 to 0.0080%> B is an element that improves the hot workability of austenitic stainless steel materials and is added as necessary. Also, B is an element that improves the secondary workability of austenitic stainless steel materials by grain boundary strengthening. From the viewpoint of obtaining the effect of B, the lower limit value of the content of B is controlled to 0.0001%, preferably 0.0003%, more preferably 0.0005%. On the other hand, if the content of B is too high, it will cause a decrease in weldability and fatigue strength. Therefore, the upper limit value of the content of B is controlled to 0.0080%, preferably 0.0040%, more preferably 0.0025%.
[0036] <Sn: 0.001 to 0.500%> Sn is an element that improves corrosion resistance and high-temperature strength and is added as necessary. From the viewpoint of obtaining the effect of Sn, the lower limit value of the content of Sn is controlled to 0.001%, preferably 0.002%. On the other hand, if the content of Sn is too high, it will form a low melting point phase and the hot workability of austenitic stainless steel materials will decrease. Therefore, the upper limit value of the content of Sn is controlled to 0.500%, preferably 0.100%, more preferably 0.050%.
[0037] <REM: 0.200% or less> REM (rare earth element) is an element that improves the hot workability of austenitic stainless steel materials in the same way as B and Ca and is added as necessary. Also, REM is an element that improves corrosion resistance by forming sulfides that are difficult to elute and suppressing the formation of MnS that serves as a corrosion initiation point. However, if the content of REM is too high, it will lead to an increase in manufacturing cost. Therefore, the upper limit value of the content of REM is controlled to 0.200%, preferably 0.100%. On the other hand, the lower limit value of the content of REM is not particularly limited, but from the viewpoint of obtaining the effect of REM, it is preferably 0.001%, more preferably 0.010%. REM is a collective term for two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanides) from lanthanum (La) to lutetium (Lu). These may be used alone or as a mixture.
[0038] In the austenitic stainless steel material according to the embodiment of the present invention, the ratio D2 / D1 of the number density D2 of inclusions having a circle-equivalent diameter of 0.5 to 10 μm at the surface (e.g., surface B in FIG. 1) to the number density D1 of inclusions having a circle-equivalent diameter of 0.5 to 10 μm in the parent phase (e.g., position C in FIG. 1) at a depth of 1 / 4 of the thickness from the surface (e.g., surface B in FIG. 1) is 0.50 or less, preferably 0.49 or less, and more preferably 0.48 or less. By controlling the ratio D2 / D1 of the number densities of inclusions within such a range, the proportion of inclusions present at the surface can be reduced compared to inclusions present in the parent phase, and therefore the corrosion resistance and fatigue properties of the austenitic stainless steel material can be improved. The lower limit of the ratio D2 / D1 of the number densities of inclusions is not particularly limited because the smaller the ratio, the greater the effect of improving the corrosion resistance and fatigue properties. For example, the lower limit is 0.01.
[0039] The number density D1 of inclusions having a circle equivalent diameter of 0.5 to 10 μm in the parent phase at a position from the surface of the austenitic stainless steel material to a depth of 1 / 4 of the thickness (hereinafter referred to as "number density D1 of inclusions in the parent phase") can be calculated as follows. First, any location (10 or more fields of view) at a position from the surface of the austenitic stainless steel material to a depth of 1 / 4 of the thickness (parent phase) is photographed with an electron microscope. Next, the photographed image is binarized to separate inclusions having a circle equivalent diameter of 0.5 to 10 μm (black) and the parent phase (white), the black regions are counted to determine the number of inclusions, and the number of inclusions obtained is divided by the area of the observation field to calculate the number density D1 of inclusions in the parent phase. Similarly, the number density D2 of inclusions having an equivalent circle diameter of 0.5 to 10 μm on the surface of an austenitic stainless steel material (hereinafter referred to as "the number density D2 of inclusions on the surface") can be calculated by photographing any location (10 or more fields of view) on the surface of the austenitic stainless steel material with an electron microscope and dividing the number of inclusions obtained in the same manner as above by the area of the observed fields of view. Here, since most of the inclusions have a circle-equivalent diameter in the range of 0.5 to 10 μm, the number of inclusions in this size range was counted and defined as the number densities D1 and D2 of the inclusions. The circle-equivalent diameter means the diameter of a circle when the area of each observed black region is converted into a circle having the same area.
[0040] As the electron microscope, a Schottky scanning electron microscope SU5000 manufactured by Hitachi High-Tech Corporation can be used. Inclusions can be identified using an EDX detector EMAX3.3SP2 manufactured by Oxford Instruments Ltd. that is attached to the electron microscope. For image processing, analysis software (AZtecSteel) manufactured by Oxford Instruments Ltd. can be used.
[0041] The number density D1 of the inclusions in the matrix is, for example, 80 to 300 pieces / mm 2 That's about it.
[0042] The number density D2 of the inclusions on the surface is preferably 75 pieces / mm 2 Less than or equal to 60 pieces / mm 2 By controlling the number density D2 of the inclusions on the surface within this range, the amount of inclusions present on the surface of the austenitic stainless steel material can be reduced, and therefore the corrosion resistance and fatigue strength of the austenitic stainless steel material can be stably improved. The lower limit of the number density D2 of the inclusions on the surface is not particularly limited because the smaller the number, the greater the effect of improving the corrosion resistance and fatigue properties. For example, 2 It is.
[0043] The inclusions are non-metallic inclusions (particularly sulfide-based and oxide-based inclusions), and specific examples thereof include MnS, TiN, TiC, NbN, NbC, CaO, SiO2, Al2O3, and complex compounds thereof.
[0044] The austenitic stainless steel material according to the embodiment of the present invention preferably has a molten and solidified layer on the surface. Here, as an example, a schematic cross-sectional view of an austenitic stainless steel material according to an embodiment of the present invention is shown in FIG. As shown in Figure 1, an austenitic stainless steel material 10 comprises a parent phase 11 and a molten solidified layer 12 formed on a surface A of the parent phase 11. The parent phase 11 contains inclusions 13. The molten solidified layer 12 may also contain inclusions 13, but there are few inclusions 13 exposed on a surface B of the molten solidified layer 12. This is because the inclusions 13 exposed on the surface B are dissolved by descaling with a laser beam.
[0045] The thickness of the molten solidified layer is not particularly limited, but is preferably 0.50 to 10.00 μm, more preferably 1.00 to 10.00 μm, and even more preferably 2.00 to 10.00 μm. If the thickness of the molten solidified layer is less than 0.50 μm, the inclusions are likely to be insufficiently dissolved. Therefore, the inclusions exposed on the surface tend to increase, and the corrosion resistance and fatigue properties of the austenitic stainless steel material tend to decrease. On the other hand, if the thickness of the molten solidified layer exceeds 10.00 μm, the surface tends to become rough, making it difficult to obtain a smooth and glossy surface.
[0046] The austenitic stainless steel material according to the embodiment of the present invention has a surface arithmetic mean roughness Ra of preferably 0.01 to 0.40 μm, more preferably 0.01 to 0.30 μm, and even more preferably 0.01 to 0.20 μm. By controlling the surface arithmetic mean roughness Ra within such a range, the smoothness of the austenitic stainless steel material can be ensured. In this specification, the term "arithmetic mean roughness Ra" refers to the arithmetic mean roughness Ra measured in accordance with JIS B0601:2013.
[0047] The austenitic stainless steel material according to the embodiment of the present invention has a 60 degree specular gloss Gs(60°) of the surface of preferably 200 to 750%, more preferably 300 to 750%, and even more preferably 400 to 750%. By controlling the 60 degree specular gloss Gs(60°) of the surface within such a range, the gloss of the austenitic stainless steel material can be ensured. In this specification, the term "60 degree specular gloss Gs(60°)" refers to the 60 degree specular gloss Gs(60°) measured in accordance with JIS Z8741:1997.
[0048] The austenitic stainless steel material according to the embodiment of the present invention is preferably an austenitic stainless cold-rolled steel material, and more preferably an austenitic stainless cold-rolled steel sheet. In this specification, the cold-rolled steel material and cold-rolled steel sheet after the oxide scale has been removed are referred to as "austenitic stainless cold-rolled steel material" and "austenitic stainless cold-rolled steel sheet", respectively, and the cold-rolled steel material and cold-rolled steel sheet before the oxide scale has been removed are referred to as "cold-rolled steel material" and "cold-rolled steel sheet". Hereinafter, an explanation will be given of a case where the austenitic stainless steel material according to the embodiment of the present invention is an austenitic stainless cold-rolled steel sheet. The thickness (sheet thickness) of the austenitic stainless cold rolled steel sheet according to one embodiment of the present invention is not particularly limited, but is preferably less than 3 mm, more preferably 2.5 mm or less, and further preferably 2 mm or less. The lower limit is, for example, 0.1 mm, and may be 0.3 mm.
[0049] The austenitic stainless cold-rolled steel sheet according to one embodiment of the present invention can be produced by using a method known in the art, except for carrying out a descaling step in which a cold-rolled steel sheet having the above-mentioned composition is irradiated with laser light to remove oxide scale formed on the surface.
[0050] The method for producing a cold-rolled steel sheet having the above composition is not particularly limited, but for example, it can be produced as follows. First, stainless steel having the above composition is melted and forged or cast to obtain a steel slab. Next, the steel slab is hot-rolled, annealed, and then descaled. The method for descaling is not particularly limited, and can be performed using pickling, polishing, or laser light. Next, the descaled hot-rolled steel sheet is cold-rolled and annealed to obtain a cold-rolled steel sheet. The conditions for each step are not particularly limited and may be appropriately adjusted depending on the composition of the stainless steel, etc.
[0051] The cold-rolled steel sheet is irradiated with laser light under conditions that allow melting of a region from the interface between the parent phase and the oxide scale in the cold-rolled steel sheet to a depth of 0.50 to 10.00 μm, preferably 1.00 to 10.00 μm, more preferably 2.00 to 10.00 μm. By irradiating with laser light under such conditions, the oxide scale can be removed while ensuring the smoothness and gloss of the surface, and the inclusions on the surface are dissolved by the heat effect to form a molten solidified layer on the surface, thereby improving the corrosion resistance and fatigue properties. If the irradiation conditions allow melting only to a region less than 0.50 μm deep from the surface of the cold-rolled steel sheet, the inclusions are not dissolved sufficiently, so that the inclusions exposed on the surface cannot be sufficiently reduced, and the corrosion resistance and fatigue properties of the austenitic stainless steel cold-rolled steel sheet are deteriorated. In addition, if the irradiation conditions allow melting of a region from the surface of the cold-rolled steel sheet to a depth of more than 10.00 μm, the surface of the austenitic stainless steel cold-rolled steel sheet becomes rough, and a smooth and glossy surface cannot be obtained.
[0052] FIG. 2 is a schematic cross-sectional view for explaining the difference between descaling by laser light irradiation and descaling by a conventional method. 2(a), a cold-rolled steel material (cold-rolled steel sheet) 20 has an oxide scale 21 formed on the surface of a parent phase 11. Also, inclusions 13 are present at an interface D between the parent phase 11 and the oxide scale 21 (the surface of the parent phase 11). When descaling (removal of oxide scale 21) is performed by a conventional method (pickling and / or polishing), inclusions 13 present at the interface D between the parent phase 11 and the oxide scale 21 are exposed at the surface E, as shown in FIG. 2(b). Even if the surface layer of the parent phase 11 is removed together with the oxide scale 21 in order to remove the inclusions 13 present at the interface D between the parent phase 11 and the oxide scale 21, the inclusions 13 present inside the parent phase 11 end up being exposed at the surface E. For this reason, it is difficult to reduce the inclusions 13 exposed at the surface E using conventional methods.
[0053] In contrast, when descaling is performed by irradiating a laser beam, as shown in FIG. 2(c), the oxide scale 21 is removed and the inclusions 13 present at the interface D between the parent phase 11 and the oxide scale 21 are dissolved. As a result, a molten solidified layer 12 is formed on the surface of the parent phase 11, and the number of inclusions 13 exposed on the surface B is reduced. The reduction in the number of inclusions 13 occurs when the inclusions 13 near the surface melt when the molten solidified layer 12 is formed, become diluted with the parent phase components, and rapidly solidify before reprecipitation. In addition, in the vicinity of the molten solidified layer 12, even in the parts that were not directly melted, the inclusions 13 are dissolved due to the increase in temperature, resulting in a reduction in the size of the inclusions 13 and a reduction in the number of the inclusions 13. Even if the inclusions are not completely melted and rendered harmless, they are partially melted and the circle equivalent diameter of the inclusions 13 is reduced, thereby improving the corrosion resistance and fatigue strength.
[0054] The conditions of the laser irradiation may be adjusted according to the device used, taking into consideration the following points. (Type of laser light) When continuous wave laser light is used, the energy required to remove the oxide scale becomes large, the required power becomes large, and the area affected by heat becomes too large, making it difficult to control the thickness of the molten solidified layer. Therefore, a pulsed laser light that can apply heat instantaneously is preferred. (wavelength) In general, the reflectance of a material to light depends on the wavelength, and selecting a wavelength with a low reflectance increases the heat input, making it easier for the oxide scale to evaporate. Therefore, by selecting a wavelength with a high reflectance for the parent phase and a low reflectance for the oxide, it is possible to selectively evaporate and remove the oxide scale without melting the parent phase more than necessary. (Pulse Width) The pulse width represents the time that one pulse is irradiated, and the narrower the pulse width, the more instantaneous heating occurs. With a narrow pulse width, ablation occurs before the heat input by the laser is transmitted to the surroundings, so the ablation threshold is smaller and the thermal impact on the parent phase is reduced. When laser irradiation is performed under conditions that cause the parent phase to melt, the narrower the pulse width, the more rapid cooling occurs and the more suppressed the reprecipitation of molten inclusions. However, the pulse width is mainly determined by the performance of the oscillator, and since devices capable of oscillating with short pulse widths are expensive, it is preferable to select a short pulse width within the specifications of the device. (oscillation frequency) The shorter the pulse width, the higher the oscillation frequency can be, and the higher the oscillation frequency, the more pulses are emitted per unit time, which improves the rate at which oxide scale is removed. Therefore, it is preferable to select a high oscillation frequency within the range of the device specifications.
[0055] (scan frequency) The scanning frequency represents the moving speed of the pulse irradiation position in the planar direction, and the higher the scanning frequency, the faster the oxide scale removal speed becomes, but if the frequency is too high, gaps will be generated between the pulse irradiation positions, and the oxide scale will remain, reducing the descaling rate. Therefore, it is preferable to increase the scanning frequency within a range where the descaling rate can be maintained. (Laser beam diameter) The larger the beam diameter, the wider the irradiation range, i.e., the range that can be descaled with one pulse, and the better the descaling efficiency, but the lower the energy density (fluence) of one pulse. It is preferable to increase the beam diameter within a range that maintains a fluence that can evaporate and remove oxide scale. (Fluence) By irradiating the laser beam with a fluence exceeding the ablation threshold of the oxides that make up the oxide scale, the oxide scale can be evaporated and removed. The higher the fluence, the greater the thickness of the oxide scale that can be removed, but if the fluence is too high, not only the oxide scale but also the parent phase will be evaporated and removed. In addition, the pulsed laser has less thermal impact than the continuous wave laser, but the higher the fluence, the greater the heat input to the parent phase, and the larger the molten and heat-affected zones will be. Therefore, the fluence can be adjusted within a range that does not melt the parent phase more than necessary, taking into account the balance between the characteristics of the oxide scale to be removed (thickness, structure, composition, etc.) and the heat input to the parent phase. If the distribution of fluence is different within the beam spot, it can be controlled using the average fluence.
[0056] The austenitic stainless steel material according to the embodiment of the present invention having the above characteristics is excellent in corrosion resistance and can be used as a corrosion-resistant member. In addition, this austenitic stainless steel material is also excellent in fatigue properties, so it is suitable for use in corrosion-resistant members that require fatigue properties. Furthermore, this austenitic stainless steel material has a smooth and glossy surface and is excellent in design, so it is suitable for use in corrosion-resistant members that require design properties.
[0057] The corrosion-resistant member according to the embodiment of the present invention includes the above-mentioned austenitic stainless steel material. The austenitic stainless steel material used for this corrosion resistant member may be processed into various shapes by methods known in the art. The corrosion-resistant member according to the embodiment of the present invention may further include members other than the above-mentioned austenitic stainless steel material. Examples of corrosion-resistant members include, but are not limited to, automobile parts, building parts, kitchen utensils, and the like. EXAMPLES
[0058] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0059] 30 kg of stainless steel having the composition of steel types A to F shown in Table 1 (the balance being Fe and impurities) was melted by vacuum melting, forged into a 30 mm thick steel billet, heated at 1230°C for 2 hours, hot rolled to a thickness of 3 mm, and annealed at 1100°C for 5 minutes in an air atmosphere to obtain a hot-rolled steel sheet. The hot-rolled steel sheet was cut into a size of 50 mm (rolling direction) x 50 mm (width direction) by processing, and then pickled and descaled. The pickled and descaled steel sheet was immersed in a hydrofluoric acid-nitric acid aqueous solution containing 50 g / L of hydrofluoric acid and 150 g / L of nitric acid in a thermostatic bath at 60°C for 120 to 1200 seconds, and then immediately washed with running water and naturally dried. The specific immersion times were 120 seconds for steel type A, 600 seconds for steel type B, 1200 seconds for steel type C, 1000 seconds for steel type D, 600 seconds for steel type E, and 1000 seconds for steel type F. The hot-rolled steel sheets were then cold-rolled from 3 mm to 1 mm in thickness and annealed at 1100°C for 5 minutes in an air atmosphere to obtain cold-rolled steel sheets. The obtained cold-rolled steel sheets were used in the following examples and comparative examples.
[0060] [Table 1]
[0061] (Examples 1 to 6) Cold-rolled steel sheets having each of the steel compositions were subjected to a descaling process by irradiation with a laser beam. The laser beam was irradiated using a commercially available device (LaserClear50A manufactured by IHI Inspection & Measurement Co., Ltd.). The cold-rolled steel sheet was placed on the movable stage of this device, and while moving at 0.2 m / min along the rolling direction, the cold-rolled steel sheet was scanned from above in the sheet width direction at a constant speed and irradiated once with the pulsed laser beam. The scan width per scan was 25 mm. The irradiation conditions for the pulsed laser beam were as follows: Wavelength: 1085nm Pulse width: 220ns Oscillation frequency: 60kHz Scan frequency: 100Hz Laser beam diameter: 90μm Average fluence: 6J / cm 2
[0062] Comparative Example 1 A cold-rolled steel sheet having the composition of steel type A was subjected to a descaling process by pickling. The pickling was carried out as follows: A hydrofluoric / nitric acid aqueous solution containing 30 g / L of hydrofluoric acid and 100 g / L of nitric acid was kept at 60° C. in a thermostatic chamber, and the cold-rolled steel sheet was immersed for 600 seconds, and then immediately rinsed with running water and naturally dried.
[0063] Comparative Example 2 Belt grinding using SiC abrasive paper (grit #400) and water-soluble grinding oil was performed on the cold-rolled steel sheet after the descaling process obtained in Comparative Example 1. The grinding depth was set to a depth of 20 μm from the surface.
[0064] The cold-rolled steel sheets (austenitic stainless steel cold-rolled sheets) after the descaling process obtained in the above examples and comparative examples were evaluated as follows.
[0065] (Inclusion density D1, D2) Test pieces of 50 mm square were cut out from the center in the width direction and length direction of the austenitic stainless cold rolled steel sheets obtained in the above examples and comparative examples, and arbitrary locations on the surface were photographed at 200x using a Schottky scanning electron microscope SU5000 manufactured by Hitachi High-Tech Corporation. The surface of this test piece was also polished to remove 1 / 4 of the thickness (250 μm) to expose the parent phase at a position 1 / 4 of the thickness from the surface, and then arbitrary locations on this exposed surface were photographed in the same manner as above. The photographs were taken from 0.48 mm × 0.64 mm (0.3072 mm) square. 2 ) was counted as one field of view, and 10 fields of view were analyzed. Next, the captured images were binarized using analysis software (AZtecSteel) manufactured by Oxford Instruments Ltd., and separated into inclusions (black) with a circle equivalent diameter of 0.5 to 10 μm and the mother phase (white). The image analysis conditions were as follows: Resolution: 4096 Minimum detection size: 8 pixels (0.5 μm) Inclusion color threshold: 47~24057 Anything less than 8 pixels was excluded as noise. Next, the number of inclusions was calculated by counting black areas with a circle equivalent diameter of 0.5 to 10 μm in the binarized image, and the number of inclusions obtained was divided by the area of the observation field to calculate the number densities D1 and D2 of the inclusions. The results of the number densities D1 and D2 of the inclusions were taken as the average values of the results in each field. In addition, the ratio of the number densities of the inclusions, D2 / D1, was calculated based on the calculated number densities D1 and D2 of the inclusions.
[0066] (Thickness of melted and solidified layer) Austenitic stainless steel cold-rolled sheet was cut in the thickness direction (direction perpendicular to the surface) parallel to the rolling direction, and the composition image of the cut surface was observed up to 10,000 times using an electron microscope. The melted and solidified layer was identified from the difference in contrast, and its thickness was measured. The thickness was measured at 10 random points, and the average value was used as the result.
[0067] (surface roughness measurement) The arithmetic mean roughness Ra of the surface of the austenitic stainless cold-rolled steel sheet was measured using a contact surface roughness meter (Surfcom 2800 manufactured by Tokyo Seimitsu Co., Ltd.) in accordance with JIS B0601:2013. The arithmetic mean roughness Ra was measured at five locations excluding the range from the end to 5 mm, with a reference length of 4 mm, and the average value was used as the evaluation result. The measurement positions were separated by 5 mm or more.
[0068] (Gloss measurement) The 60-degree specular gloss Gs (60°) of the surface of the austenitic stainless steel cold-rolled steel sheet was measured using a gloss meter (PG-1M manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS Z8741:1997. The 60-degree specular gloss Gs (60°) was measured at five points excluding the range of 5 mm from the end, and the average value was used as the evaluation result. The measurement positions were separated by 5 mm or more.
[0069] (Corrosion resistance test) The corrosion resistance test was conducted in accordance with JASO M609 and M610. Specifically, a salt-dry-wet cycle test was conducted in which salt spray, drying, and wetting were repeated. In the salt-dry-wet cycle test, austenitic stainless steel cold-rolled steel sheets were sprayed with 5% NaCl aqueous solution (2 hours at 35°C), dried (4 hours at 30% relative humidity and 60°C), and wetting (2 hours at 95% relative humidity and 50°C) in one cycle. After each cycle, the sheets were washed with water and dried, and the surface of the austenitic stainless steel cold-rolled steel sheets was observed and the rust area ratio was calculated. The number of cycles at which the rust area ratio became 10% or more was regarded as the number of cycles at which corrosion occurred. The calculation of the rust area ratio was carried out as follows. After the salt-dry-wet cycle test, the surface of the austenitic stainless cold-rolled steel sheet was photographed, and the ratio of the area of the rusted part in a central 25mm x 25mm area excluding the edges was calculated. The area of the rusted part was calculated by binarizing the photograph of the surface of the austenitic stainless cold-rolled steel sheet using image analysis, calculating the area per pixel, and then counting the number of pixels in the rusted part. The rust area ratio was calculated using the following formula. Rust area rate (%) = Area of rusted part (mm 2 ) / Total observation area (625mm 2 ) x 100 In this evaluation, the improvement rate of the number of cycles to corrosion occurrence was calculated for the austenitic stainless cold rolled steel sheets of Examples 1 to 6 and Comparative Example 1, based on the number of cycles to corrosion occurrence for the austenitic stainless cold rolled steel sheet of Comparative Example 2. The improvement rate of the calculated number of cycles to corrosion occurrence was evaluated as "Good" when it was 20% or more and less than 20%, as "Good" when it was 10% or more and less than 20%, and as "Poor" when it was less than 10%.
[0070] (Fatigue property test) The fatigue property test was performed in accordance with JIS Z2275:1978 by a plane bending fatigue test. Specifically, a test piece was obtained by cutting a piece of austenitic stainless steel cold-rolled sheet with a width of 30 mm and a length of 90 mm in the rolling direction, and forming a R part with a radius of 30 mm on both ends in the width direction. This test piece was attached to a plane bending tester and subjected to a bending test for 10 repetitions. 7The fatigue test was carried out 10 times. This fatigue test was carried out on two or more test pieces for each stress step, and the time strength was measured. In this evaluation, the improvement rates of time strength were calculated for the austenitic stainless cold rolled steel sheets of Examples 1 to 6 and Comparative Example 1, based on the fatigue strength of the austenitic stainless cold rolled steel sheet of Comparative Example 2. The calculated improvement rates of time strength of 10% or more were marked as "good", and those less than 10% were marked as "poor". The results of the above evaluations are shown in Table 2.
[0071] [Table 2]
[0072] As shown in Table 2, the austenitic stainless cold rolled steel sheets of Examples 1 to 6, in which the ratio D2 / D1 of the number densities of inclusions is 0.50 or less, have a surface arithmetic mean roughness Ra of 0.01 to 0.40 μm and a surface 60-degree specular gloss Gs(60°) of 200 to 750%, and are confirmed to have a smooth and glossy surface. In addition, the austenitic stainless cold rolled steel sheets of Examples 1 to 6 have improved corrosion resistance and fatigue properties compared to the austenitic stainless cold rolled steel sheet of Comparative Example 2. In contrast, the austenitic stainless cold-rolled steel sheet of Comparative Example 1 was descaled by pickling, and therefore the ratio D2 / D1 of the number densities of inclusions exceeded 0.50. Therefore, the austenitic stainless cold-rolled steel sheet of Comparative Example 1 did not have sufficiently improved corrosion resistance and fatigue properties compared to the austenitic stainless cold-rolled steel sheet of Comparative Example 2.
[0073] As can be seen from the above results, the present invention can provide an austenitic stainless steel material having a smooth and glossy surface and excellent corrosion resistance and fatigue characteristics, a manufacturing method thereof, and a corrosion-resistant component using the same. [Explanation of symbols]
[0074] 10 Austenitic stainless steel 11 Mother phase 12 Melted and solidified layer 13 Inclusions 20 Cold rolled steel 21 Oxide scale
Claims
1. The composition includes, on a mass basis, C: 0.001 to 0.150%, Si: 1.00% or less, Mn: 2.50% or less, P: 0.050% or less, S: 0.0300% or less, Ni: 6.00 to 26.00%, Cr: 15.00 to 26.00%, Mo: 8.00% or less, Cu: 4.00% or less, N: 0.400% or less, Al: 0.400% or less, Si+2Al is less than 1.20%, and the balance is Fe and impurities; An austenitic stainless steel material in which the ratio D2 / D1 of the number density D2 of inclusions at the surface to the number density D1 of inclusions having a circle equivalent diameter of 0.5 to 10 μm in a parent phase at a position 1 / 4 of the thickness from the surface is 0.50 or less, and the number density D2 of the inclusions at the surface is 75 pieces / mm2 or less.
2. The austenitic stainless steel material according to claim 1, further comprising, on a mass basis, one or more selected from Ti: 0.001 to 0.500%, Nb: 0.001 to 1.000%, V: 0.001 to 1.000%, W: 0.001 to 1.000%, Zr: 0.001 to 1.000%, and Co: 0.001 to 1.200%.
3. The austenitic stainless steel material according to claim 1 or 2, further comprising, on a mass basis, one or more selected from Ca: 0.0001 to 0.0100%, B: 0.0001 to 0.0080%, Sn: 0.001 to 0.500%, and REM: 0.200% or less.
4. The austenitic stainless steel material according to any one of claims 1 to 3, wherein the arithmetic mean roughness Ra of the surface is 0.01 to 0.40 µm.
5. The austenitic stainless steel material according to any one of claims 1 to 4, wherein the 60 degree specular gloss Gs(60°) of the surface is 200 to 750%.
6. The austenitic stainless steel material according to any one of claims 1 to 5, comprising a molten and solidified layer on the surface.
7. The austenitic stainless steel material according to claim 6, wherein the thickness of the molten solidified layer is 0.50 to 10.00 μm.
8. A method for producing the austenitic stainless steel material of claim 1, comprising the steps of: The method includes a descaling process of irradiating a cold-rolled steel material having a composition, on a mass basis, of C: 0.001 to 0.150%, Si: 1.00% or less, Mn: 2.50% or less, P: 0.050% or less, S: 0.0300% or less, Ni: 6.00 to 26.00%, Cr: 15.00 to 26.00%, Mo: 8.00% or less, Cu: 4.00% or less, N: 0.400% or less, Al: 0.400% or less, Si+2Al is less than 1.20%, and the balance is Fe and impurities, with a laser beam to remove oxide scale formed on the surface of the cold-rolled steel material, The laser beam is irradiated under conditions that allow the region of the cold-rolled steel material to be melted to a depth of 0.50 to 10.00 μm from the interface between the parent phase and the oxide scale.
9. A method for producing the austenitic stainless steel material according to claim 2, comprising the steps of: The cold-rolled steel further contains, by mass, one or more selected from Ti: 0.001 to 0.500%, Nb: 0.001 to 1.000%, V: 0.001 to 1.000%, W: 0.001 to 1.000%, Zr: 0.001 to 1.000%, and Co: 0.001 to 1.200%. The method according to claim 8.
10. A method for producing the austenitic stainless steel material according to claim 3, comprising the steps of: The cold-rolled steel further contains, by mass, one or more selected from Ca: 0.0001 to 0.0100%, B: 0.0001 to 0.0080%, Sn: 0.001 to 0.500%, and REM: 0.200% or less. The method according to claim 8 or 9.
11. A corrosion-resistant member comprising the austenitic stainless steel material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Improvement treating method for nitric acid resistance on surface of stainless alloy
JP1988089616A
Surface treatment for stainless steel
JP1990145785A
Stress corrosion cracking resistant austenitic material and its manufacture
JP1993065530A
Manufacturing method of stainless steek strip
JP2014172077A
Stainless steel for automobile exhaust system component fastening component
JP2016204714A